Anatomical variability and histological structure of the ulnar nerve in the Guyon’s canal - Depukat, Paweł (Arch Orthop Trauma Surg, 2016)
OBJECTIVES: The goal of our study was to analyze the prevalence of variations, branching patterns, and histology of the ulnar nerve (UN) in Guyon’s canal to address its importance in hand surgery, particularly decompression of the UN. METHODS: Fifty fresh cadavers were dissected bilaterally, and the nerve in the area of Guyon’s canal was visualized. Samples for histology were also taken and prepared. The collected data were then analyzed. RESULTS: Morphometric measurements of the hands and histological studies were not found to have significant differences when compared by left or right side or by sex. Three major branching patterns were found, with division into deep and superficial UN being the most common (85%). Additional findings included a majority (70%) presenting with a cutaneous branch within the canal and/or with an anastomosis of its distant branches with those of the median nerve (57%). CONCLUSION: The UN is most commonly found to divide into a superficial and deep ulnar branch within Guyon’s canal. However, additional branches and anastomoses are common and should be taken into careful consideration when approached during surgery in the area, particularly during decompression procedures of Guyon’s canal.